Non-contact ACL injuries in female athletes: an International Olympic Committee current concepts statement - Renstrom, P.; Ljungqvist, A.; Arendt, E.; Beynnon, B.; Fukubayashi, T.; Garrett, W.; Georgoulis, T.; Hewett, T. E.; Johnson, R.; Krosshaug, T.; Mandelbaum, B.; Micheli, L.; et al. (British Journal of Sports Medicine, 2008)
The incidence of anterior cruciate ligament (ACL) injury remains high in young athletes. Because female athletes have a much higher incidence of ACL injuries in sports such as basketball and team handball than male athletes, the IOC Medical Commission invited a multidisciplinary group of ACL expert clinicians and scientists to (1) review current evidence including data from the new Scandinavian ACL registries; (2) critically evaluate high-quality studies of injury mechanics; (3) consider the key elements of successful prevention programmes; (4) summarise clinical management including surgery and conservative management; and (5) identify areas for further research. Risk factors for female athletes suffering ACL injury include: